Influence of drinking water containing Aloe vera (Aloe barbadensis Miller) gel on growth performance, intestinal microflora, and humoral immune responses of broilers - Shokraneh, Meisam (Vet World, 2016)
AIM: The risk of bacteria resistance to specific antibiotics possibly by continuous subtherapeutical administration of antibiotic growth promoters (AGPs) in poultry feed led to a ban on the use of AGP in poultry production. As a result of this ban, alternative substances for poultry growth promotion and disease prevention are being investigated, among which phytogenic and herbal products have received increased attention as natural additives because they have been accepted by consumers as natural additives. The effect of water supplementation of Aloe vera (AV) as an AGP substitute on performance, intestinal microflora, and immune responses of broilers. MATERIALS AND METHODS: The five experimental treatments were allocated to four replicates. The following treatments were applied (1) a basal broiler diet (C) and normal drinking water, (2) 0.5% AV gel in drinking water, (3) 0.75% AV gel in drinking water, (4) 1% AV gel in drinking water, and (5) diet C supplemented with flavophospholipol at 4.5 mg/kg and drinking normal water. Vaccines against influenza disease and sheep red blood cell (SRBC) were administrated to immunological stimuli. The populations of Lactobacilli spp. and coliforms were enumerated in ileum. RESULTS: Body weight of broilers supplemented with different levels of AV increased compared with control group (p<0.05). Birds supplemented with antibiotic had the best feed-to-gain ratio (F:G) in different periods. Supplementation of 0.5% and 0.75% AV improved F: G entire experimental period compared with control group (p<0.05). Coliform bacteria were reduced in broilers supplemented with different levels of AV or antibiotic (p<0.05). The Lactobacilli spp. population in birds supplemented with 0.75%, 1% AV or antibiotic significantly was higher than other groups (p<0.05). Supplementation with 1% AV led to greater antibody titers against SRBC compared with other groups (p<0.05). CONCLUSION: These findings demonstrated a possibility of supplementing broiler drinking water with 1% AV gel as an alternative for AGP substitution.